Diversity of Fireflies (Coleoptera: Lampyridae) in Phitsanulok Province - โพธิ์นาค เกียรติศักดิ์; คงเจริญ พัทธเมธา; พูลประสริฐ พิสิษฐ์ (YRU Journal of Science and Technology, 2018)
This research aimed to survey the species diversity and habitat of firefly in Phitsanulok province. Firefly survey from five main different habits including abandoned land, rubber plantation, lotus pool, paddy field and canal area were carried out by using sweep net during the period 7.00 pm. to 9.00 pm between November, 2016 to September, 2017. The results showed that five lampyrid species and two morphospecies under two subfamilies i.e. 1) Luciolinae (Sclerotia aquatilis, Trisinuata sp., Medeopteryx sp., Asymmetricata circumdata and Asy. ovalis ) and 2) Lampyrinae (Pyrocoelia praetexta and Lamprigera tenebrosa) were found in this study. For the rubber plantation, four lampyrid species namely, P. praetexta, L. tenebrosa, Asy. circumdata and Medeopteryx sp. could be observed. Additionally, S. aquatilis was only one species that could be displayed in several zones i.e. lotus pool, paddy field and canal area and could be also seen throughout the observation. Based on diversity indices, the Shannon diversity (H’), evenness (E) and dominance index (D) for all lampyrids obtained from the pooled data set of this observation were 1.028, 0.574 and 0.53, respectively. For similarity index (Ss), the assemblage recorded of lampysids among different habitats shared ranging from 0.33-1.00. Moreover, it was revealed that the accumulation curve in all study sites of lampyrids was still increasing slightly when the survey stopped. It was possible that the firefly species would be raised if we continue to observe more in those areas. The basic data from this current study was able to be used as guideline in managing the area in order to further natural resources conservation.